Subcutaneous zygomycosis: A diagnostic and therapeutic challenge - Ketki Chaudhary; Kritika Agrawal; Vijay Paliwal; Puneet Bhargava; Deepak Kumar Mathur (Indian Journal of Paediatric Dermatology, 2022)
Subcutaneous zygomycosis is a rare deep fungal infection caused by a group of fungus belonging to the order Entomophtharales. It is a saprophytic fungus and the predominant species causing the infection includes Basidiobolus ranarum and Conidiobolus coronatus. We, hereby, report a case of a 17-month-old female child who presented with a painless, solitary, woody hard enlarging mass which was disfiguring the left side of the face for 6 months. After our complete workup, a diagnosis of subcutaneous zygomycosis was made. The patient was managed on syrup Itraconazole and potassium iodide drops. The patient responded to the trreatment remarkably. We would like to present our take on workup and treatment of a solitary painless enlarging mass on the face in a child.